Work conditions and morbidity among coal miners in Guachetá, Colombia: The miners' perspective (2015)
Introduction: Investigations in Colombia about work and health conditions in coal mining are scarce and few have focused on the perception of the exposed population and their behaviors in response to inherent risks. Objective: To determine the association between work conditions and the perception of morbidity among coal miners in Guachetá, Cundinamarca. Materials and methods: A cross-sectional study was performed with 154 workers selected randomly from the total registered with the municipality. Information about social and demographic characteristics and work and health conditions in the mines was gathered. The prevalence was estimated for respiratory, musculoskeletal and auditory disorders. The associations between certain work conditions, and events with a prevalence over 30% were explored using bivariate and multivariate analyses with Poisson regressions with robust variance. Results: Workers were mostly men. Ages ranged from 18 to 77 years. Most frequently reported health problems were: back pain (46.1 %), pain in an upper limb (40.3%), pain in a lower limb (34.4 %), andrespiratory (17.5 %) and auditory problems (13.6 %). Significant differences in perception were found depending on time on the job and underground or ground work conditions. Conclusions: The most recognized risks were those associated with musculoskeletal disorders since they were closer in time to the work performed (time discount). Some actions to identify psychological traits are proposed in order to improve risk perception among coal miners.